Surveilling and Securing the Olympics From Tokyo 1964 to London 2012 and Beyond - Bajc, Vida.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book analyses the relationship between the Olympic Games, with its ethos of openness and collectivism, and the security concerns and surveillance technologies that are becoming increasingly prevalent in the organisation of public events.
Keywords: Science; Science; Science, general; Electronic books